IMPLEMENTASI PENDIDIKAN KARAKTER ANAK USIA DINI MELALUI SENTRA IMTAQ - Farhatin Masrurah; Venty Angli Wardhani (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Universitas Ibrahimy, 2021)
Character building in children is an education that teaches character, morals, behavior and personality. The center of faith and piety (IMTAQ) is a learning activity that aims to enable students to develop religious abilities from an early age and to form intelligent individuals and behave according to religious norms. The focus of this research is how to plan character building through IMTAQ learning centers, how to implement character building through IMTAQ learning centers, how children's character through learning activities at IMTAQ centers. The method used in this study is a descriptive qualitative approach. The data collection techniques are interviews, observation, and documentation. While the results of this study include; 1) learning planning forms good character/noble character as stated in the main vision of the school and is integrated into semester, weekly, and daily planning. 2) implementation of character building through IMTAQ learning centers in the form of habituation activities for 18 characters in IMTAQ learning centers in accordance with BBCT guidelines, which are supported by habituation of children's religious characters. 3) children's character changes through imtaq center learning are children can be polite and always do good habits and have a fairly good religious character.